Post-concussion symptoms three months after mild-to-moderate TBI: characteristics of sick-listed patients referred to specialized treatment and consequences of intracranial injury. (29th July 2021) - Fure, Silje Christine Reistad; Howe, Emilie Isager; Spjelkavik, Øystein; Røe, Cecilie; Rike, Per-Ola; Olsen, Alexander; Ponsford, Jennie; Andelic, Nada; Løvstad, Marianne
ABSTRACT: Objective : To present pre-injury, injury-related, work-related and post-injury characteristics, and to compare patients with and without traumatic intracranial abnormalities, in a treatment-seeking sample with persistent post-concussion symptoms (PPCS) after mild-to-moderate TBI. Methods : Cross-sectional design in the context of a specialized TBI outpatient clinic. Eligible patients were aged 18–60 years, employed ≥ 50% at time of injury, and sick listed ≥ 50% at inclusion due to PPCS. Data were collected 8–12 weeks after injury through review of medical records, semi-structured interviews, questionnaires, and neuropsychological screening. Results : The study included 116 patients, of whom 60% were women, and predominantly white-collar workers in full-time positions. Ninety-four percent had a mild TBI, and 23% had intracranial abnormalities. The full sample reported high somatic, emotional, and cognitive symptom burden, and decreased health-related quality of life. Patients with normal CT/MRI results reported higher overall symptom burden, while patients with intracranial abnormalities had worse memory function. Conclusion : Injury severity and traumatic intracranial radiological findings should not be the sole ground for planning of rehabilitation service provision in patients with PPCS, as subjective complaints do not necessarily co-vary with these variables.